Evaluating the Efficacy of Houttuynia cordata Leaf Meal in Enhancing Growth in Silver Carp (Hypophthalmichthys molitrix) Fingerlings - Murasing, Samir; Yadav, M.K; Saxena, Shriparna; Kher, Deepak (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
To evaluate the effects of Houttuynia cordata (fish mint) leaf meal on the growth performance of H. molitrix fingerlings, a 45-day feeding trial was carried out. Four experimental diets containing 0%, 3%, 6%, and 9% H. cordata leaf meal were formulated, representing three treatment groups and one control. Each treatment was replicated three times. Growth performance indicators, including net weight gain, percent weight gain, Length gain, specific growth rate (SGR), feed conversion ratio (FCR), were evaluated. Findings revealed that incorporating fish mint leaves in the diet had a posstive impact on growth performance. Silver carp fed with 6 % treatment T3 fish mint leaves exhibited the highest average weight gain (49.2±0.166g), percent weight gain (52.8±1.301g), length gain (17.8±1.154) and specific growth rate (0.86±0.005), with improved feed conversion ratio (3.18±0.024). Interestingly, growth performance declined when fish mint leaves were included at 3% and 9% in the diet, implying that higher concentrations might have adverse effects.These results suggest that 6% inclusion of H. cordata leaf meal can enhance growth performance in silver carp fingerlings.